2021
DOI: 10.1016/j.redox.2021.102162
|View full text |Cite
|
Sign up to set email alerts
|

LIN28a induced metabolic and redox regulation promotes cardiac cell survival in the heart after ischemic injury

Abstract: Rationale Cell-based therapeutics have been extensively used for cardiac repair yet underperform due to inability of the donated cells to survive in near anoxia after cardiac injury. Cellular metabolism is linked to maintenance of cardiac stem cell (CSC) renewal, proliferation and survival. Ex vivo expansion alters (CSC) metabolism increasing reliance on oxygen dependent respiration. Whether promoting ‘metabolic flexibility’ in CSCs augments their ability to survive in near anoxia and repair the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 43 publications
2
7
0
Order By: Relevance
“…They found that LIN28AB enhances, while let-7 suppresses, aerobic glycolysis by targeting pyruvate dehydrogenase kinase 1 (PDK1), demonstrating a novel pathway to mediate aerobic glycolysis of cancer cells [116]. In accordance with a previous study, Yuko et al showed that LIN28A therapeutic effect on CTSCs was linked to the let-7/PDK1 signaling pathway [117]. Insight into the exact mechanisms of the LIN28/let-7 axis could enable the manipulation of cellular pluripotency and diseases such as diabetes and cancer.…”
Section: Network Of Lin28ab Targetssupporting
confidence: 65%
See 2 more Smart Citations
“…They found that LIN28AB enhances, while let-7 suppresses, aerobic glycolysis by targeting pyruvate dehydrogenase kinase 1 (PDK1), demonstrating a novel pathway to mediate aerobic glycolysis of cancer cells [116]. In accordance with a previous study, Yuko et al showed that LIN28A therapeutic effect on CTSCs was linked to the let-7/PDK1 signaling pathway [117]. Insight into the exact mechanisms of the LIN28/let-7 axis could enable the manipulation of cellular pluripotency and diseases such as diabetes and cancer.…”
Section: Network Of Lin28ab Targetssupporting
confidence: 65%
“…Furthermore, CTSC-LIN had a significantly increased amount of antioxidant markers and reduced ROS generation compared to the control (CTSC-GFP). In addition, CSTC-LIN showed an increased ability to secrete pro-reparative paracrine factors under hypoxic conditions and promote cardiomyocyte proliferation and survival after ischemic cardiac injury [117]. In other words, LIN28 makes adult cardiac stem cells more metabolically flexible, significantly improving their chances of survival.…”
Section: The Lin28ab As a Molecular Target In Treating Injuries And D...mentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of let-7 has been shown to increase with age in cardiac stem-like cells (CSLC). Following treatment of CSLC with a let-7 mimic, their proliferation was significantly reduced ( 52 ). Angiogenesis is repressed by overexpression of let-7 and by silencing of the let-7 target gene HMGA2 in EC ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…ELAVL1 plays an important role in inhibiting hyperglycemia-induced cardiomyocyte pyroptosis and regulating ferroptosis in myocardial injury [51,52]. LIN28A is also implicated in various cardiac injuries or diseases [53,54]. NEAT1 (ENSG00000245532) produces a lncRNA that may act as a transcriptional regulator for numerous genes.…”
Section: Candidate Gene Expression Features Discriminating Different ...mentioning
confidence: 99%